Niyamatana (financial institution): Epigraphical evidence on an ancient banking system inthe kingdom of Anurādhapura in Sri Lanka. - MA Zhongwu , N.S.Gunawardana (South Eastern European Journal of Public Health, 2025)
This study investigates the Niyamatana financial system, an ancient banking and granary network in the kingdom of Anurādhapura, as revealed through multiple inscriptions, including the TōnigalaKaludiyapokuṇa, Labuäṭabäňdigala andEppāvala inscription records. Dating from the 4th to 10th centuries C.E., these inscriptions detail how deposits of grains, beans, and currency were used to generate interest, supporting monastic activities such as the vassa festival. The integration of merchants and monks in managing these financial institutions highlights the advanced economic structures in ancient Sri Lanka, predating similar systems in South Asia.